The COVEG score to predict severity and mortality among hospitalized patients with COVID-19 - Mohamed El-Kassas; Maha El Gaafary; Mohamed Elbadry; Mohamed Ahmed Medhat; Hany Dabbous; Essam Ali Hassan; Ahmed Abdelmoaty; Haidi Karam-Allah; Hamdy Sayed; Amr Abdalazeem; Ahmed Fouad Sherief; Eman Fares; et al. (Journal of Infection in Developing Countries)
Introduction: COVID-19 severity and mortality predictors could determine admission criteria and reduce mortality. We aimed to evaluate the clinical-laboratory features of hospitalized patients with COVID-19 to develop a novel score of severity and mortality.